ZEP Quiz sebagai Media Video Game Edukatif: Upaya Meningkatkan Motivasi Belajar Fikih Siswa Madrasah Ibtidaiyah - Winda Dwi Lestari; Eti Hadiati; Evi Febriani (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Students’ learning motivation in Fiqh instruction at Madrasah Ibtidaiyah remains a persistent concern when the learning process is predominantly characterized by conventional teaching methods and reliance on textbooks. Such conditions may lead students to become less active, less enthusiastic, and insufficiently engaged in comprehending religious subject matter. This study aims to analyze the effect of using ZEP Quiz-based video game media on the learning motivation of fourth-grade students in Fiqh instruction at Madrasah Ibtidaiyah Negeri 2 Bandar Lampung. Employing a quantitative approach, this study adopted a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of 56 fourth-grade students, comprising 28 students in the experimental class who received instruction using ZEP Quiz-based video game media and 28 students in the control class who received conventional instruction. Data were collected using a Likert-scale learning motivation questionnaire administered in the form of pretest and posttest. The data were analyzed using normality tests, homogeneity tests, N-Gain analysis, and an Independent Sample t-test through SPSS. The findings revealed that the mean learning motivation score of students in the experimental class increased from 64.20 to 84.47, while the control class increased from 61.85 to 74.77. The t-test results indicated a significance value of 0.005 < 0.05, demonstrating a significant difference between the two groups. Therefore, ZEP Quiz-based video game media is empirically proven to enhance students’ learning motivation in Fiqh instruction.